2020
DOI: 10.12669/pjms.36.7.3056
|View full text |Cite
|
Sign up to set email alerts
|

Common Cancers in Karachi, Pakistan: 2010-2019 Cancer Data from the Dow Cancer Registry

Abstract: Objectives: To present 2010-2019 cancer data from the Dow Cancer Registry representing all districts of Karachi (~17.4 million). Methods: The study was conducted at the Dow University of Health Sciences. After ethical approval, the Dow Cancer Registry was established at the largest government-run diagnostic and reference center of Karachi (Dow Labs). All cancers registered during 2010-2019 were analyzed. Patients >18years of age were labeled as adults while those with ages ≤18years were classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Cancer registrations at the DCR were sourced from Dow Labs, which collect cancer specimens from around the city via 34 collection points in Karachi. 4 , 5 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer registrations at the DCR were sourced from Dow Labs, which collect cancer specimens from around the city via 34 collection points in Karachi. 4 , 5 …”
Section: Methodsmentioning
confidence: 99%
“…Collection of data and data indexation was performed as already reported. 4 , 5 All cancer diagnoses were confirmed via histopathology and coded as per ICD10 coding guidelines. All data were indexed initially using MS Excel as well as SPSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, a pathology-based cancer registry of Dow University of Health Sciences (DUHS) listed NMSC, as the fifth most commonly diagnosed cancer (being second most common in males and fifth most common in females), suggesting a substantial increase of skin cancer burden in Karachi. 6 Reported cases in Karachi and Larkana are far common than in other parts of Pakistan (like Hazara-district) proving the wellestablished fact that there exists an inverse relation between skin cancer incidence and distance from the equator. 7 Taken together, these data suggest an increase of skin cancer throughout Pakistan in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Qureshi et al in 2016 reported 6-year (2010-2015 cancer data from the Dow Cancer Registry which represents the largest public sector diagnostic and reference laboratory of the city (Qureshi et al,2016). More recently, another report from the Dow Cancer Registry detailed cancer patterns in Karachi during 2010-2019(Qureshi et al, 2020. Importantly, revival of the KCR was announced in a recent report which describes cancer patterns in Karachi during 2017 -2019(Pervez et al, 2020.…”
mentioning
confidence: 99%